2010
DOI: 10.19030/ajbe.v3i2.382
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences In Attitudes Toward Computers And Performance In The Accounting Information Systems Class

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-size: 10pt;"><span style="font-family: Times New Roman;">Using a model developed by Young (2000), this paper explores the relationship between performance in the Accounting Information Systems course, self-assessed computer skills, and attitudes toward computers.<span style="mso-spacerun: yes;">&nbsp; </span>Results show that after taking the AIS course, students experience a change in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In relation to computers and accounting, McDowall and Jackling (2006) found that gender was not a significant influence on academic performance in computer-based courses -a finding later supported (Bove˜e et al, 2007). Lenard et al (2010) also noted that there was no significant difference in the self-ranking of computer skills between males and females in the beginning of an accounting information's systems class; yet, by the end, females' self-assessment improved significantly. Guiller and Durndell (2006) reported that online discussions have meant that females are now more likely to take part in voluntary discussion groups, and post more messages, and these tended to be more positive in nature.…”
Section: Factorsmentioning
confidence: 95%
“…In relation to computers and accounting, McDowall and Jackling (2006) found that gender was not a significant influence on academic performance in computer-based courses -a finding later supported (Bove˜e et al, 2007). Lenard et al (2010) also noted that there was no significant difference in the self-ranking of computer skills between males and females in the beginning of an accounting information's systems class; yet, by the end, females' self-assessment improved significantly. Guiller and Durndell (2006) reported that online discussions have meant that females are now more likely to take part in voluntary discussion groups, and post more messages, and these tended to be more positive in nature.…”
Section: Factorsmentioning
confidence: 95%
“…Lenard el at. [12] explored the gender differences in performance in the Accounting Information Systems course. However, they focused on assessing the students' IT skills rather than the systems analysis and design skills.…”
Section: Introductionmentioning
confidence: 99%